Prevalence and determinants of thrombocytopenia in newborn unit at Alexandria University Hospital: a three-year report including 1000 patients - Marwa Mohamed Farag; Mohamed Hazem Goda; Hanan Fawzy Nazir; Ahmed Akram Deghedy (BMC Pediatrics)
Abstract Background Thrombocytopenia might be the only clinical clue of diseases in neonates. Classification of thrombocytopenia according to severity, onset offset, nadir and duration might help in identification of the etiology. Aim This study aims to estimate the prevalence and, identify the determinants and patterns of thrombocytopenia among neonates. Method An observational retrospective cohort study was conducted and included records of neonates admitted to neonatal intensive care unit of Alexandria University Maternity Hospital. Data were collected using a checklist and analyzed by SPSS version 20.0. Chi square test and independent sample t- test were used to compare different variables between thrombocytopenic and non- thrombocytopenic patients. Logistic regression analysis was carried out in order to identify the independent contribution of various maternal and neonatal variables influencing thrombocytopenia and factors impacting mortality in thrombocytopenic patients. Results Four-thousands five hundred neonates, were randomized to have sample of 1011 neonates to be included in the analysis. Patients were divided into thrombocytopenic group (n = 375) and thrombocytopenic group (n = 636). Gestational age and birthweight were significantly lower in thrombocytopenic group with p values < .001 and .03, respectively. Necrotizing enterocolitis, early onset sepsis and late onset sepsis were the main determinants of neonatal thrombocytopenia with OR (95% CL), 2.25 (1.25–3.98), 4.8 (3.249–7.19) and 6.567(4.083–10.562). severe intraventricular hemorrhage, pulmonary hemorrhage and cardiovascular instability were main predictors of death in thrombocytopenic patients with OR (95% CL), 4 (1.9–8.34), 20.9 (6.7 -64.9), and 5.76 (2.1–15.8), respectively. Conclusion Identification of severity and patterns of thrombocytopenia can help the clinician to recognize the etiology and consequently optimize management of thrombocytopenic neonates.